The connection and background mechanisms of social fears and problematic social networking site use: A structural equation modeling analysis - Zsido, Andras N. (Psychiatry Res, 2020)
Previous research warned that internet and social media use could have a negative effect on the social lives of excessive users. Based on the social compensation hypothesis, however, factors related to social fears could lead to problematic social networking site (SNS) use because individuals try to compensate for their offline popularity. It was shown that individuals with higher levels of social fears tend to prefer computer-mediated (CMC) instead of face to face (FTF) communication. Here, we aimed to create a model that shows the direct and indirect effects of social anxiety and self-esteem on problematic SNS use. A total of 215 participants filled out our survey including measures of social anxiety, self-esteem, fear of negative evaluation, social media and Internet addiction. Using structural equation modeling we tested the indirect and direct effects between the variables. Our results indicated that social anxiety and lower self-esteem could lead to favoring CMC over FTF communication, which may result in problematic internet (PIU) and SNS use as a compensatory behavior to cope with fear of negative evaluation. The indirect pathways might highlight relevant differences behind the motivation of PIU – anonymity – and problematic SNS use – control. Theoretical as well as practical implications are discussed.